Cell-penetrating Peptides for Cancer-targeting Therapy and Imaging - Wang, Weiqin; Abbad, Sarra; Zhang, Zhenhai; Wang, Shu; Zhou, Jianping; Lv, Huixia (Current Cancer Drug Targets, 2015)
Cell-penetrating peptides (CPPs) have been previously shown to be powerful transport vector tools for the delivery of a large variety of cargoes through the cell membrane, as well as other physiological membranes. And since they’re relatively cell-, receptor- and energy-independent, CPPs have unique advantages in facilitating drugs entry into cells. This paper briefly reviews the discovery, mechanism and classification of CPPs, and especially focuses on the specific limitations of CPPs and their potential applications for tumor-targeted delivery of biologically active molecules, imaging agents and carriers.
Keywords: Cell penetrating peptides